Fabrication of pH/Reduction Sensitive Polyethylene Glycol-Based Micelles for Enhanced Intracellular Drug Release - Yang Yang; Fuwei Yang; Xiaotian Shan; Jiamin Xu; Wenjie Fang; Juan Zhou; Lipeng Qiu; Jinghua Chen (MDPI AG, 2021)
At present, the drug is still difficult to release completely and quickly only with single stimulation. In order to promote the rapid release of polymeric micelles at tumor site, pH/reduction sensitive polymers (PCT) containing disulfide bonds and orthoester groups were synthesized. The PCT polymers can self-assemble in water and entrap doxorubicin to form drug-loaded micelles (DOX/PCT). In an in vitro drug release experiment, the cumulative release of DOX/PCT micelles in the simulated tumor microenvironment (pH 5.0 with GSH) reached (89.7 ± 11.7)% at 72 h, while it was only (16.7 ± 6.1)% in the normal physiological environment (pH 7.4 without GSH). In addition, pH sensitive DOX loaded micellar system (DOX/PAT) was prepared as a control. Furthermore, compared with DOX/PAT micelles, DOX/PCT micelles showed the stronger cytotoxicity against tumor cells to achieve an effective antitumor effect. After being internalized by clathrin/caveolin-mediated endocytosis and macropinocytosis, DOX/PCT micelles were depolymerized in intercellular acidic and a reductive environment to release DOX rapidly to kill tumor cells. Additionally, DOX/PCT micelles had a better inhibitory effect on tumor growth than DOX/PAT micelles in in vivo antitumor activity studies. Therefore, pH/reduction dual sensitive PCT polymers have great potential to be used as repaid release nanocarriers for intercellular delivery of antitumor drugs.